Durability of the agricultural producer’s workshop as an objective of support under selected activities of the Rural Development Programme 2014-2020 - Kazimierczuk, Marcin (Przegląd Prawa Rolnego, 2020)
The deliberations focus on the analysis of regulations included in the Rural Development Programme 2014-2020 concerning the instruments of support for investments that prevent destruction and restore the potential of agricultural production. They aim at answering the question whether and to what extent these forms of support protect the agricultural producer and ensure the durability of his workplace. The author argues, among other things, that two of them: “Investments aimed at protecting waters against nitrate pollution from agricultural sources” and “Support for investments in preventive measures aimed at reducing the effects of probable natural disasters, adverse climatic events and catastrophes,” owing to favourable financing conditions and clear legal regulations introduced, contribute to an increased protection of farmers’ interest by adopting specific attitudes towards active risk management in agricultural activity, and thus increase their resilience to emerging crisis situations. In the case of “Restoring the potential of agricultural production damaged by natural disasters” however, this tool does not significantly affect the protection of the agricultural producers’ workplaces and requires legislative changes.